Studi kelayakan sarana dan prasarana pembelajaran olahraga dan kesehatan tingkat SMPN se-Kecamatan Praya - Aulia, Willa; Maulidin, Maulidin (Universitas Hamzanwadi, 2023)
The purpose of this study was to examine the condition and ownership status of physical education facilities and infrastructure in junior high schools throughout the Praya district. This study used the entire population of 6 SMPN. By using a population study sampling technique. The instrument used in this study is the observation sheet. The data analysis technique in this study used a quantitative descriptive analysis method, namely data processing by the number of available facilities multiplied by 100% for the ideal number of facilities. The results of the research for SMPN 1 are 67.11% in the adequate category, SMPN 2 72% in the adequate category, SMPN 3 43.11% in the category sufficient enough, and SMPN 4 29.77% in the inadequate category, SMPN 5 73.77% in the adequate category, SMPN 6 69.77% adequate category. Meanwhile, the average calculation result for all physical education facilities and infrastructure in junior high schools in Praya District is 59.25% in the quite adequate category. The conclusion of this study is that there are 3 schools in the adequate category of infrastructure, SMPN 1 has a field area of 3600 m2, SMPN 2 has a field area of 2007 m2, SMPN 3 has a field area of 1080 m2. Inadequate category infrastructure 3 schools SMPN 4 field area 465 m2, SMPN 5 field area 675 m2, SMPN 6 field area 150 m2.